Role of plaque in the clearance of salivary sucrose and its influence on salivary ph - A Kumar; R Hedge; U Dixit (Wolters Kluwer Medknow Publications, 2011)
Background: The prevalence of dental caries in children, in India, is higher than many of the industrialized countries. The sugar most commonly associated with dental caries is sucrose, as the microorganisms in the dental plaque have the ability to convert this dietary constituent into various organic acids. Aims and Objectives: This study was conducted to study the effect of the presence of plaque on the salivary clearance of sucrose and to study the effect of the presence of plaque on salivary pH, following sucrose clearance. Materials and Methods: Salivary sucrose determination was done by using the anthrone technique. A Digital MHOS pH meter estimated the salivary pH. Results: Presence of plaque increased the salivary sucrose clearance time and decreased the salivary pH at various time intervals. Conclusions: The microbial etiology of dental caries is the dynamic relationship among the dental plaque microbiota, dietary carbohydrates, saliva and pH lowering, and the cariogenic potential of the dental plaque. Caries occur preferentially in the dentition sites characterized by high exposure to carbohydrate and diminished salivary effect.